Promoting Inquiry-Based Teaching in Laboratory Courses: Are We Meeting the Grade? - Beck, Christopher (American Society for Cell Biology, 2014)
Over the past decade, repeated calls have been made to incorporate more active teaching and learning in undergraduate biology courses. The emphasis on inquiry-based teaching is especially important in laboratory courses, as these are the courses in which students are applying the process of science. To determine the current state of research on inquiry-based teaching in undergraduate biology laboratory courses, we reviewed the recent published literature on inquiry-based exercises. The majority of studies in our data set were in the subdisciplines of biochemistry, cell biology, developmental biology, genetics, and molecular biology. In addition, most exercises were guided inquiry, rather than open ended or research based. Almost 75% of the studies included assessment data, with two-thirds of these studies including multiple types of assessment data. However, few exercises were assessed in multiple courses or at multiple institutions. Furthermore, assessments were rarely based on published instruments. Although the results of the studies in our data set show a positive effect of inquiry-based teaching in biology laboratory courses on student learning gains, research that uses the same instrument across a range of courses and institutions is needed to determine whether these results can be generalized.